THE ROLE OF ETHICS IN BUILDING A SUSTAINABLE BUSINESS ENVIRONMENT IN THE DIGITAL ERA - Yanita; Atika Sulistia (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
The digital era brings new challenges to the business world, especially in the application of ethical principles and the creation of a sustainable business environment. This article discusses the importance of the role of ethics in dealing with the development of digital technology and its impact on various aspects of business. ethics are a moral foundation that not only regulates business behavior but also increases trust and credibility in the eyes of stakeholders. Business ethics in the digital era are not only limited to basic principles such as honesty and fairness, but also include data management, data protection, and digital responsibility. Cases of corporate ethics violations such as the Enron scandal show the importance of transparency and accountability in the digital era. In addition, the integration of technologies such as big data, AI, and blockchain has increased the operational efficiency of companies while maintaining high ethical standards. New challenges in the digital business environment, such as cybersecurity and privacy threats, require careful and ethical management. Business leaders play a critical role in building ethical organizations, especially in decision-making that impacts the sustainability of the business and society as a whole. Therefore, this article emphasizes that the application of ethics in business is important not only to achieve short-term profits, but also to create long-term sustainability that benefits everyone involved.